THE REVOLUTION AS A DEMOCRATIC APORIA: SANDINISTA POLITICAL LANGUAGE AND THE CONSTITUTION OF AN EXCLUSIONARY IMAGINARY IN NICARAGUA, 1979-1984 - Ugalde Barrantes , Daniel (2025)
This article offers an historical-conceptual reading of the political language of the Sandinista Revolution, focusing on the way in which the concept of revolution was articulated with the notions of “sovereign people” and “revolutionary legitimacy” in Nicaragua during the period 1979–1984. The study argues that, in the Nicaraguan context, the revolution operated as both a legitimizing and exclusionary concept. Furthermore, it delineated the boundaries of the political community and defined who could speak in the name of the nation. From this perspective, the notion of “the people” not only expressed a particular form of sovereignty but also crystallized a democratic aporia in which the pursuit of revolutionary unity culminated in the denial of political diversity. The research concludes that the Sandinista political language—by linking revolution, sovereignty, and nation within a single language—produced an exclusionary national imaginary, revealing the tensions between representation, participation, and legitimacy that traverse Latin American revolutionary democracies of the twentieth century.